Faktor Penghambat Penegakan Hukum Terhadap Pengangkutan Hasil Tambang Ilegal - Roy Djordy Satingi; Fenty Puluhulawa; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
Illegal mining itself is a mining activity or extracting agricultural products carried out by the community or a business entity or we can call it a company where this activity does not have a business permit and also does not use the principles regarding how to mine in accordance with existing regulations or not. use mining methods properly and correctly. The basic mining laws that apply in Indonesia are stated in the Mining UlUl Number 3 of 2020 concerning amendments to UlUl Number 4 of 2009 concerning Mineral and Coal Mining, mining excavation itself consists of several types. Starting from strategic minerals or group a minerals, vital minerals or group c, and finally, group c minerals. In Indonesia itself we can certainly find cases of illegal mining in various regions, that is why enforcement efforts should be carried out as best as possible in order to reduce the growth rate of existing illegal mining which of course is to guarantee or increase state income through existing mining businesses. certainly legal in the eyes of the law.